(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article offers a critical analysis of Brazilian forensic science as a technology of racial surveillance, highlighting how forensic practices contribute to the technical-scientific legitimation of institutional violence against Black and marginalized populations. Drawing on an interdisciplinary literature review, the article articulates critical criminology, sociology of science, and decolonial studies to demonstrate that forensic knowledge—far from neutral—is shaped by historical structures of racialization, penal selectivity, and epistemic exclusion. Special attention is given to the role of algorithmic technologies and artificial intelligence in the production of forensic reports and judicial decisions, revealing how such systems, when trained on biased datasets, exacerbate racial inequality under the guise of objectivity. The research underscores the urgency of an antiracist forensic reform, grounded in epistemic justice and in the pluralization of truth regimes regarding death and violence.